Atrazine and Diuron Effects on Survival, Embryo Development, and Behavior in Larvae and Adult Zebrafish - Zaluski, Amanda B.; Wiprich, Melissa T.; de Almeida, Luiza F.; de Azevedo, Andressa P.; Bonan, Carla D.; Vianna, Monica R. M. (Frontiers in Pharmacology, 2022)
Atrazine and Diuron are widely used herbicides. The use of pesticides contaminates the aquatic environment, threatening biodiversity and non-target organisms such as fish. In this study, we investigated the effects of acute exposure for 96 h hours to atrazine and diuron commercial formulations in zebrafish (Danio rerio, wild-type AB) embryos and larvae and adult stages. We observed a significant concentration-dependent survival decrease and hatching delays in animals exposed to both herbicides and in the frequency of malformations compared to the control groups. Morphological defects included cardiac edema, tail reduction, and head malformation. At 7 days post-fertilization (dpf), atrazine exposure resulted in a reduction in the head length at 2, 2.5, and 5 mg/L and increased the ocular distance at 1, 2, 2.5, and 5 mg/L atrazine when compared to controls. At the same age, diuron increased the ocular distance in animals exposed to diuron (1.0 and 1.5 mg/L) and no effects were observed on the head length. We also evaluated a behavioral repertoire in larvae at 7 dpf, and there were no significant differences in distance traveled, mean speed, time in movement, and thigmotaxis for atrazine and diuron when animals were individually placed in a new environment. The cognitive ability of the larvae was tested at 7 dpf for avoidance and optomotor responses, and neither atrazine nor diuron had significant impacts when treated groups were compared to their corresponding controls. Adults’ behavior was evaluated 7 and 8 days after the end of the acute herbicide exposure. Exploration of a new environment and associated anxiety-like parameters, social interaction, and aggressiveness were not altered. Our results highlight the need for further studies on the sublethal effects of both herbicides and the consideration of the effects of commercial formulas vs. isolated active ingredients. It also emphasizes the need to take sublethal effects into consideration when establishing the environmental limits of residues.